Autonomous University in Brazil: A Utopia? - Fávero, Maria de Lourdes de Albuquerque (Education Policy Analysis Archives, 1999)
The purpose of this work is to trace the historical stages through which university autonomy in Brazil has evolved. It begins with 1931 when Minister Francisco Campos conceded "relative autonomy" to the universities and describes developments to the present day. The history of autonomy in Brazilian universities is related to various political regimes and national movements through which Brazil has passed in the last 70 years. Final thoughts on the the challenges facing academic autonomy in present-day Brazil are presented.